Efficacy of an internet-based intervention for burnout: a randomized controlled trial in the German working population. Issue 2 (4th March 2017) - Jonas, Benjamin; Leuschner, Fabian; Tossmann, Peter
ABSTRACT: Background and Objectives: Internet-based interventions are a viable treatment option for various mental problems. However, their effects on the burnout syndrome yielded mixed results. In this paper, we examine the efficacy of a structured and therapist-guided internet intervention, based on solution-focused and cognitive-behavioral therapy, for individuals with symptoms of burnout. Design: Two-arm, Internet-based, randomized, wait-list controlled trial (RCT). Methods: Participants were recruited through in-house events and online advertising. They were randomly assigned to the intervention or a wait-list. Group comparison was conducted three months after randomization. Outcomes were the burnout level according to the Maslach Burnout Inventory (MBI-GS) and the levels of depression, anxiety and stress according to the DASS-21. Results: Thirty-nine participants were included in the trial; 36 (92.3%) took part at the 3-months-follow-up. Intention-to-treat analyses revealed significant group differences in favor of the intervention group in depression ( d = 0.66), cynicism ( d = 0.87) and personal accomplishment ( d = 0.75). Conclusions: The intervention helped ameliorate symptoms of work-related stress and burnout. Although limited by a small sample size, the study suggests that the program provides effective support for affected individuals. However, further studies with bigger sample sizes should be conducted to examine the effects of such programs more precisely.